A Complexidade da Administração/Gestão Escolar, Limites e Possibilidades - Militão, Andréia Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This thesis was developed by the Program of Graduate Studies in Education of the Faculty of Science and Technology / Universidade Estadual Paulista and is linked to the research line Public Policy, School Organization and Teacher Education. It had as its object of analysis administration / management that takes place in schools. We take for granted that the School Administration / Management as field of knowledge was played by two opposing views: one that advocated that this was dependent on the General Theory of Administration; and another, who defended the specificity of School Administration. Throughout the twentieth century, these two concepts have polarized the debate on the School Administration / Management and hegemonized the field. The first seeks to put it as a mainly technical activity, prevalent in the 1960s and 1970s; the second emerges from the 1980s, seeking the specificity of Administration / School management, enhancing its political dimension. This treatment resulted, in the studies field and even in the formulation of educational policies, the sidelining of its pedagogical dimension. We seek to answer the question: What are the limits and possibilities of action of the administration / school management in the context of a state school in the state of São Paulo? Departig from this problem, we seek to answer the following guiding research questions: What are the characteristics that differentiate the school administration / management of business administration? What are the concepts underlying the concepts of school administration / management present in the formulations of SEE / SP? How do the technical, political and pedagogical dimensions interact within school administration / management?...

A presente tese foi desenvolvida junto ao Programa de Pós-Graduação em Educação da Faculdade de Ciências e Tecnologia/Universidade Estadual Paulista e encontra-se vinculada à linha de pesquisa Políticas Públicas, Organização Escolar e Formação de Professores, teve como objeto de análise a administração/gestão que se realiza no âmbito escolar. Tomamos como pressuposto que a Administração/Gestão Escolar, enquanto campo do conhecimento foi disputada por duas concepções opostas: uma que advogava que esta era tributária da Teoria Geral da Administração; e, outra, que defendia a especificidade da Administração Escolar. Ao longo do século XX, estas duas concepções polarizaram os debates sobre a Administração/Gestão Escolar e hegemonizam o campo. A primeira procura situá-la como atividade preponderantemente técnica, prevalece nas décadas de 1960 e 1970; a segunda desponta a partir dos anos 1980, buscando a especificidade da Administração/Gestão escolar, valorizando a sua dimensão política. Esse tratamento provocou no campo de estudos e mesmo na formulação das políticas públicas educacionais, a secundarização da sua dimensão pedagógica. Procura-se responder a questão: Quais os limites e as possibilidades de atuação da administração/gestão escolar no contexto de uma escola estadual paulista? A partir desse problema, buscamos responder as seguintes questões norteadoras da pesquisa: Quais as características que diferenciam a administração/gestão escolar da administração de empresas? Quais os conceitos que embasam as concepções de administração/gestão escolar presentes nas formulações da SEE/SP?...
Keywords: Educação; Escolas - Organização e administração; Políticas públicas; Ensino; Education